The mystery of the hidden house - Blyton, Enid (London : Dean, 2015)
Where could Mr Goon's nephew have disappeared to? Mr Goon has forbidden the Five Find-Outers from solving mysteries - so they decide to make one up for his nephew, Ern! But what will happen when Ern disappears, and their pretend mystery turns into a real one?
Keywords: Children's stories -- Fiction